2001
DOI: 10.4049/jimmunol.167.7.3785
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoprotein Promotes Mature Dendritic Cell Transition from Differentiating Monocyte

Abstract: Proinflammatory oxidized phospholipids are generated during oxidative modification of low-density lipoproteins (LDL). The production of these proinflammatory oxidized phospholipids is controlled by secreted enzymes that circulate as proteins complexed with LDL and high-density lipoprotein. During the acute phase response to tissue injury, profound changes occur in lipoprotein enzymatic composition that alter their anti-inflammatory function. Monocytes may encounter oxidized phospholipids in vivo during their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 50 publications
4
116
0
1
Order By: Relevance
“…Additionally, the continued high expression of MHC class II and costimulatory CD86 molecules on DCs, but not on microglia and macrophages, suggests that these DCs may remain capable of presenting myelin Ag, even if devoid of IFN-γ signaling. Interestingly, it has been shown that oxidized lipids induce a mature phenotypic signature in DCs with up-regulation of CD86, whereas at the same time phagocytic activity is inhibited (60). Similarly, oxidized lipids have been shown to promote the differentiation of a macrophage cell line into a DC phenotype in vitro (61), as is consistent with our data showing an increase in the number of DCs in IFN-γR −/− mice and WT mice treated with anti-IFN-γ mAb.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the continued high expression of MHC class II and costimulatory CD86 molecules on DCs, but not on microglia and macrophages, suggests that these DCs may remain capable of presenting myelin Ag, even if devoid of IFN-γ signaling. Interestingly, it has been shown that oxidized lipids induce a mature phenotypic signature in DCs with up-regulation of CD86, whereas at the same time phagocytic activity is inhibited (60). Similarly, oxidized lipids have been shown to promote the differentiation of a macrophage cell line into a DC phenotype in vitro (61), as is consistent with our data showing an increase in the number of DCs in IFN-γR −/− mice and WT mice treated with anti-IFN-γ mAb.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the presence of oxidized LDL during monocyte differentiation to DC yielded phenotypically and functionally mature DC (11). Optimal reactivity of monocytes was obtained when oxLDL was added during late stages of differentiation in GM-CSF and IL-4.…”
Section: Cd86 Expression Induced By Lipophilic Molecules Of Oxldlmentioning
confidence: 99%
“…It is accompanied by alterations in lipoprotein composition that result in generation of oxidized low density lipoprotein (oxLDL) and oxidized phospholipids [3,4]. OxLDL were first studied for their role in chronic inflammation during atherosclerosis [5] but recent work indicates that infection and inflammation also result in increased levels of oxLDL [6] and modified lipids that can be detected by the immune system [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Sensing the danger is a crucial function of Ag-presenting cells, that is necessary to initiate primary immune responses [35,36]. We previously hypothesized that oxLDL and modified phospholipids such as LPC generated during APR could signal the presence of a dangerous situation to the immune system and showed that oxLDL and LPC could favour the development of adaptive immunity by promoting mature DC generation in vitro [7][8][9]. It is shown here that LPC can prime both cellular and humoral Ag-specific responses, confirming that the APR regulates the production of critical immunoregulatory molecules by controlling the biochemical composition of lipoproteins.…”
Section: Introductionmentioning
confidence: 99%